Investigation on the pregnant women's fear of childbirth and analysis of its influencing factors (孕妇分娩恐惧现状调查及影响因素分析) - JIN Zijun (靳紫君); SUI Tingting (隋婷婷); WEI Ying (魏莹); TAO Lingwei (陶领伟); WANG Yanzhi (王艳芝) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the pregnant women's fear of childbirth and its influencing factors, and analyze the relationship between fear of childbirth and social support. Methods A convenient sample of 101 pregnant women were recruited and investigated by using a self-made general information questionnaire, the Chinese version of Childbirth Attitudes Questionnaire (CAQ) and Perceived Social Support Scale (PSSS). Results The dimension score of fetal health was higher than other three dimension of CAQ. There was a significant difference in CAQ score between pregnant women with different employment status(P＜0. 01). There was no correlation between social support level and fear of childbirth among pregnant women. Conclusion Findings of the study showed a high awareness of fetal health among pregnant women, and employment status is a potential influencing factor of attitude toward childbirth. Targeted interventions are required to improve the social support of women. (目的 调查孕妇对分娩的恐惧感以及个体因素对其影响程度, 分析孕妇分娩恐惧与社会支持的相关性。方法 采用方便抽样选取住院的101名孕妇为研究对象, 收集孕妇一般资料和产科相关资料, 和使用分娩恐惧量表(CAQ)调查孕妇对分娩的恐惧感, 使用领悟社会支持量表(PSSS)调查孕妇社会支持程度。结果 CAQ量表4个维度中胎儿健康维度得分较高。不同职业的孕妇中文版CAQ总分差异有统计学意义(P＜0. 01)。社会支持与孕妇分娩恐惧之间缺乏相关性。结论 孕妇对胎儿健康的关注度高于其本身, 孕妇的职业状况影响孕妇对分娩的恐惧感。应制定针对性干预措施提升孕妇社会支持。)